2013
DOI: 10.1016/j.crohns.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infliximab therapy on transmural lesions as assessed by magnetic resonance enteroclysis in patients with ileal Crohn's disease

Abstract: Improvement of MRE occurs from 2 weeks after infliximab therapy onwards and correlates with clinical response but normalization of MRE is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…Moreover, similarly to previously recently published data [51], the authors did not observe a complete healing of the lesions and most of the patients had persistent signs of inflammation and lesions at SICUS, which had improved but were not resolved after biological therapy.…”
Section: Sicussupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, similarly to previously recently published data [51], the authors did not observe a complete healing of the lesions and most of the patients had persistent signs of inflammation and lesions at SICUS, which had improved but were not resolved after biological therapy.…”
Section: Sicussupporting
confidence: 77%
“…Anti-tumour necrosis factor (TNF) a agents are effective in the treatment of Crohn's disease CD because they can induce clinical remission and mucosal healing in most patients. Nevertheless, CD is a transmural process and data on transmural healing induced by these molecules are still lacking [50][51][52][53]. A recent study has evaluated transmural healing, which is defined as normalization of bowel wall thickening, using bowel sonography in patients with CD treated with biologics and immunosuppressors and its correlation with clinical remission and mucosal healing [52].…”
Section: Sicusmentioning
confidence: 99%
“…In a small preliminary series, Van Assche et al [72] reported that the complete resolution of transmural lesions after anti-TNF therapy is rarely observed, even the authors observed a progressive improvement of MR parameters of activity, thus confirming previous results [73]. More recently, Ordás et al [13] were able to observe the normalization of the transmural MR alterations, including wall thickness, edema, mural hypervascularization and extra-mural lesions, in patients achieving endoscopic mucosal healing 12 weeks after the start of anti-TNF.…”
Section: Ultrasoundmentioning
confidence: 96%
“…Other MRE-based indexes for detecting activity in CD have also been proposed [65][66][67][68][69][70][71][72]. Among these, the score purposed by Hyun et al [12] includes parameters similar to those in the MaRIA score, but the variables are grouped and graded into three degrees of severity and the gold standard consists of both double-balloon endoscopy and ileocolonoscopy, thus allowing evaluation of the whole intestine.…”
Section: Magnetic Resonance Enterographymentioning
confidence: 99%